Potensi dan skema pemanfaatan sumber daya alam di Kampung Armopa Distrik Bonggo Kabupaten Sarmi Provinsi Papua: Potential and schemes for utilizing natural resources in Armopa Village, Bonggo District, Sarmi Regency, Papua Province - Pono, Wahyudi Sayuti; Hendri; Dwiranti, Febriza; Ap, Aris Toteless; Kende, Henoch (IGKOJEI: Jurnal Pengabdian Masyarakat, 2025)
ABSTRACT  Armopa is one of the indigenous communities village in Bonggo Sarmi district Papua province. This village is located at the coastal areas, netx to the river stream where mangrove ecosystem is growing. This community service was designed to identify and mapp the natural resources available in this village and design an appropriate and suitable technology, skills, and end-products that macths with the local resources, demand, market to get an optimum added value to the lovcal commnutiies. Field survey and intensive interview were conducted to collect the data. The results show that coconut, Pandanus Anggur Papua, Merbau, Matoa timber, Candle nut, mangrove and Bali cattle are the dominant natural resources recorded in Armopa village. Fifty one schemes of utilizations are identified and determined, ranging rom foods, beverage, raw material for various processed foods, handy craft, small entrepreneurship business, and ecotourism. There are two sub commodities with the multiple schemes of Coconut and mangrove ecosystem. Gaining an added values for local commnunities and governments, the productions of end-used products with local wisdom is the most feasible approach to be adopted. Training, skill update, management and finance capacaity building are various activity needed to deliver to the local community to achieve the sustainability for their resources and utilizations. Collaborative actions and participations from various background and dicplines are required to deliver this programs, from researchers, university student, Non-government organization, funding agency, and the others.   Keywords: Beverage; edu-ecotourism; foods; local communities; and small entreprenetureship   ABSTRAK  Kampung Armopa distrik Bonggo memiliki topograpi landai kaya dengan sumberdaya pesisir dan dataran rendah tropis, serta berlokasi pada jalan nasional yang mengubungkan ibu kota provinsi Papua dengan kota kabupaten seribu ombak Sarmi. Kampung Armopa dibawah areal kerja Kesatuan pengelolaan Hutan produksi (KPHP) Bonggo.  Kegiatan pengabdian kepada masyarakat ini (PkM) bertujuan untuk mengidentifikasi potensi sumberdaya alam dominan di dekat pemukiman masyarakat lokal Armopa dan membuat skema pemanfaatannya menggunakan pendekatan pemberdayaan masyarakat lokal. PkM dilakukan dengan survey lapangan, wawancara dan diskusi dengan tokoh masyarakat, kepala kampung dan staf KPHP Bonggo. Hasil PkM menunjukkan bahwa tiga komoditas utama di kampung Armopa meliputi sektor Pertanian, Kehutanan, dan Peternakan. Sektor pertanian terdiri dari dus sub komoditas yaitu Kelapa dan buah Pandan anggur Papua, Kehutanan terdiri dari olahan kayu Merbau, Matoa, hasil hutan bukan kayu buah Kenari dan ekosistem mangrove. Sedangkan untuk sektor peternakan adalah sapi bali. Skema pemanfaatan tiga sektor tersebut menghasilkan sebanyak 51 skema pemanfaatan mulai dari produk minuman, makanan, bahan baku industri makanan, bahan kerajinan, hasil olahan usaha kecil mikro dan menengah (UMKM) dan ecowisata. Berbagai skema pemanfaatan tersebut dikembangkan dengan memperimbangkan ketrampilan dan penguasaan teknologi serta kearifan masyarakat lokal Armpoa. Produk-produk hilirisasi akan memberikan multi dampak (multiple added values) bagi masyarakat, pemerintah daerah dan pengelolaan sumberdaya alam di Armopa, seperti pekerjaan, kesempatan berusaha, dan  pendapatan bagi masyarakat lokal. Kerjasama dan kolaborasi berbagai pihak sangat diperlukan untuk menunjang keberlanjutan kegiatan hilirisasi pemanfaatan sumberdaya alam untuk kesejahteraan dan pemberdayaan masyarakat lokal di Armopa. Kata kunci: Amorpa; hilirisasi; masyarakat lokal; nilai tambah; dan sumberdaya alam